Goethite Nanofibers as Bio-Fillers in Dental Composite Resin - Dhanasekaran Sihivahanan1,Vidyashree Nandini2 , E.Rajesh3 , N.Anitha3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Composite resins represent an important member of biomaterials family that have been evolving due tothe needs in biocompatibility and mechanical properties. Fillers in a variety of forms and types have beenevaluated and the impact of fillers to improve the performance of the dental composites have been studiedin vast. Various composite resin fillers tested had revealed its own strengths and weaknesses. Bio polymerswhen they are reinforced with biofillers can produce novel biocomposites. The biocomposites with thebiofillers will replace and be a substitute for synthetic fibre-reinforced composites. In recent years, naturalbio-fibres have gained attention as suitable reinforcements in polymeric matrices. These bio-fillers possesshigh specific strength and can be effectively used for dental composites resin. The most commonly occurringnatural bio-fibres are the teeth of limpets. The teeth of limpets have a distinctive composite nanostructurewhich comprises of high-volume fractions of reinforcing goethite nanofibers to provide mechanical integrity.The limpet tooth is effective at resisting failure to abrasion. The goethite nanofibers are expected to besignificant for novel dental biomaterials with extreme strength and hardness.